o APLICAÇÃO DA ESCALA DE AVALIAÇÃO DO USO DE FRALDAS EM UMA CLÍNICA MÉDICA DE UM HOSPITAL UNIVERSITÁRIO (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objectives: apply the evaluation scale for the use of diapers and absorbent products (AUFA Scale) in patients admitted to the medical clinic; identify and analyze the results of this application, the sociodemographic profile of patients in vogue as well as repercussions on the skin related to the use of sanitary pads and diapers. Method: observational, cross-sectional, descriptive and exploratory study, carried out in the medical clinic sector of the University Hospital Hospital Universitário Clementino Fraga Filho (HUCFF/UFRJ), from November 2019 to February 2020, with a convenience sample of 46 patients. There was application of a form to survey general data and, later, the application of the AUFA scale, which identified the following variables: skin conditions, skin aging, cognitive ability, motor skills and incontinence. Results: all 46 patients were using diapers, half women and the other half men, mostly elderly and without a diagnosis of incontinence. In view of the application and analysis of the AUFA scale, only 18 patients (39.14%) were indicated for diaper use. With the inappropriate use of diapers, 27 patients had skin lesions resulting from moisture, a situation that was justified by the absence of systematic care observation for the prevention and treatment of dermatitis associated with incontinence in the evaluated patients. Conclusion: the use of the AUFA scale is indicated to identify patients who need to wear diapers, delimiting care with their management and thus preventing complications and worsening of incontinence.